Storing JWT Token in Local Variables - Bulgakova, O.S.; Zosimov, V.V.; Popravkin, P.D. (Control systems & computers, 2020)
The article discusses the problem of storing structured information over the Internet (JSON format) in local storage and pieces of information transmitted to the browser from the site visited by the user (cookies), and a method is proposed for storing the JSON web key in a local variable inside the closure (functions that refer to into independent variables). Based on user authorization, the interaction of the JSON web key with the server is shown, and the solution to the main problems of authorization and storage of the token JWT (JSON Web Token). Здійснено порівняння варіантів збереження JSON веб-ключа. Зіставлено приклади наявності токена в зоні ризику CSRF та XSS атак. Описано алгоритм формування системи безпеки з використанням JSON веб-ключа, збереженого в локальній змінній всередині замикання. Проведено сравнение вариантов сохранения JSON веб ключа. Проведено сравнение вариантов хранения JSON веб ключа и опасность CSRF и XSS атак на представленные методы. Описан алгоритм формирования системы безопасности с использованием JSON веб ключа сохраненном в локальной переменной внутри замыкания.